Answer:
Step-by-step explanation:
It will be whichever equation you see that has the "c" = +3, in the format:
F(x) = y = ax^2 + bx + c, where a, b, and c are all integers, such that plugging a "0" into the x's will give:
y = a•0^2 + b•0 + 3 = 0 + 0 + 3 = 3
Total area = 9 x5 =45
Total area = (6+3)(4+1)=24+6+12+3=45
Answer:
84x^10
Step-by-step explanation:
The coefficients multiply, and the exponents add.
(4x)( -3x^6)(-7x^3) = (4)(-3)(-7)x^(1+6+3) = 84x^10
__
The rule for exponents is ...
(x^a)(x^b) = x^(a+b)
Answer:
Provide question
Step-by-step explanation:
Provide question